The Machine at Utopia's Center. - Williams, Lynn F. (Utopian Studies, 1991)
The article discusses the literary works on communities based on a natural and criticizes the use of machines in such works including "Ectopia", "Woman on the Edge of Time", and "A Door into Ocean." Topics include depiction of pseudo-natural environment, use of a machine that symbolizes God in such works, and failure of creating an utopian environment.